2018
DOI: 10.1523/jneurosci.0669-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Synapse Development byVgatDeletion from ErbB4-Positive Interneurons

Abstract: GABA signaling has been implicated in neural development; however, in vivo genetic evidence is missing because mutant mice lacking GABA activity die prematurely. Here, we studied synapse development by ablating vesicular GABA transporter in in ErbB4-positive (ErbB4+) interneurons. We show that inhibitory axo-somatic synapses onto pyramidal neurons vary from one cortical layer to another; however, inhibitory synapses on axon initial segments (AISs) were similar across layers. On the other hand, PV-positive (PV+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 97 publications
1
26
0
1
Order By: Relevance
“…ErbB4 is present at postsynaptic sites of excitatory synapses onto inhibitory neurons and is implicated in their formation (3,4,8). We investigated whether these synapses are altered by adult ErbB4 deletion by using Vglut1 and PV antibodies to label, respectively, presynaptic excitatory terminals and postsynaptic dendrites of PV+ interneurons, many of which are ErbB4+ (4,13,15,16). As shown in SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ErbB4 is present at postsynaptic sites of excitatory synapses onto inhibitory neurons and is implicated in their formation (3,4,8). We investigated whether these synapses are altered by adult ErbB4 deletion by using Vglut1 and PV antibodies to label, respectively, presynaptic excitatory terminals and postsynaptic dendrites of PV+ interneurons, many of which are ErbB4+ (4,13,15,16). As shown in SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 H and I), indicating compromised GABA release probability. Besides perisomatic synapses, ErbB4+ neurons also form inhibitory synapses onto axon initial segments (AISs) of pyramidal neurons (3,4,16). Adult deletion seemed to have no effect on the number of these synapses (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The donor animals also carried the Cre-dependent tdTomato reporter allele R26-Ai14 to allow the visualization of the cells in which Cre-mediated recombination occurred. It is well established that synaptic GABA release is absent in cells of the floxed Vgat mouse line that express cre recombinase (Wojcik et al, 2006;Tong et al, 2008;Saito et al, 2010;Vong et al, 2011;Wu et al, 2012;Pei et al, 2015;Hirano et al, 2016;Lin et al, 2018;Weaver et al, 2018). Loss of VGAT from presynaptic regions in MGE-derived interneurons was further assessed in vitro using immunohistochemistry of long-term cultures of Vgat ϩ/ Ϫ and Vgat Ϫ/Ϫ MGE cells.…”
Section: Transplanted Mge-derived Cortical Interneurons With Vgat Losmentioning
confidence: 99%
“…Decreased VGAT density, as well as increased bouton size or vesicle disorganization further suggest impairment of presynaptic GABAergic terminals. On its own, decreased VGAT density might explain a reduction of synapses throughout the cortical layers 76 and lead to impaired loading of GABA in the presynaptic vesicles 59 . Importantly, Sahadevan, Hembach and collaborators performed studies in Fus ∆ NLS/+ mice at earlier ages and also observed early defects of inhibitory synapses, as early as 1 month of age and progressive at 6 months of age (Sahadevan, Hembach et al, co-submitted manuscript).…”
Section: Discussionmentioning
confidence: 99%